Post-intubation airway related adverse effects: a comparison between intra-cuff dexamethasone and intra-cuff alkalinized lignocaine. - Kep, Kee W; Nadia MN,; Melvin K,; Muhammad M,; Raha AR,; Nurlia Y, (Department of Surgery, UKM Medical Centre, 2013)
Post-intubation airway related adverse effects such as coughing on the endotracheal tube (ETT), restlessness, hoarseness and sore throat are common and undesirable outcomes of anaesthesia using endotracheal intubation. This prospective randomized single blind study was carried out to compare the effectiveness of intra-cuff dexamethasone and alkalinized lignocaine in reducing the incidence of post-intubation airway related adverse effects. Eighty four patients aged 18 – 60 years, of ASA status I or II, were randomly allocated into three groups: air, dexamethasone and alkalinized lignocaine. Their ETT cuffs were inflated according to the group they were allocated to. The incidence of coughing on the ETT, restlessness, hoarseness and sore throat was assessed, postoperatively. The results showed a significant difference in the incidence of cough, restlessness, hoarseness and sore throat in the dexamethasone group compared to the air group. All the patients had minimal or no sore throat at all documented times. Both intra-cuff dexamethasone and alkalinized lignocaine significantly reduced the incidence of hoarseness. However, alkalinized lignocaine additionally lowered the incidence of restlessness, significantly.